2006
DOI: 10.1063/1.2177649
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale simulation of morphology in hydrated perfluorosulfonic acid membranes

Abstract: Current fuel cell proton exchange membranes rely on a random network of conducting hydrophilic domains to transport protons across the membrane. Despite extensive investigation, details of the structure of the hydrophilic domains in these membranes remain unresolved. In this study a dynamic self-consistent mean field theory has been applied to obtain the morphologies of hydrated perfluorosulfonic acid membranes (equivalent weight of 1100) as a model system for Nafion at several water contents. A coarse-grained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
3
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 59 publications
12
150
3
1
Order By: Relevance
“…Nevertheless, Wescott et al 100 found that, in common with the DPD simulations of Yamamoto and Hyodo 94 there was a reasonable agreement between the absolute cluster sizes predicted by SCMFT and those observed in scattering experiments. Significantly, they found a linear increase in characteristic size scale of the morphologies with increasing water content, which provides a counterexample to earlier suppositions that this must necessarily imply a lamellar morphology.…”
Section: Mesoscale Modelsmentioning
confidence: 62%
“…Nevertheless, Wescott et al 100 found that, in common with the DPD simulations of Yamamoto and Hyodo 94 there was a reasonable agreement between the absolute cluster sizes predicted by SCMFT and those observed in scattering experiments. Significantly, they found a linear increase in characteristic size scale of the morphologies with increasing water content, which provides a counterexample to earlier suppositions that this must necessarily imply a lamellar morphology.…”
Section: Mesoscale Modelsmentioning
confidence: 62%
“…The commercial force field COM-PASS was used, and their potential parameters were listed in the literature. 19,43,44 All of the molecular simulations were carried out using a Hewlett-Packard workstation and the Material Studio software package (Accelrys Inc., CA, U.S.A.).…”
Section: Simulation Proceduresmentioning
confidence: 99%
“…For PEMs, extensive studies have been carried out to investigate their peculiar structures and proton transport behavior. 19,20 Paddison used ab initio strategy to study proton dissociation of the sulfonic acid group in triflic acid and p-toluene sulfonic acid, simulating Nafion and PEEKK models, respectively. 21 Later, he and Elliott performed ab initio calculations to investigate proton dissociation of the short side chain of a perfluorosulfonic acid membrane such as Nafion and the resulting proton transfer with solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Wescott et al [45], for example, performed mesoscale simulations of hydrated Nafion using a self-consistent mean field theory approach and a coarse-grained model, deriving the interaction parameters from classical MD. In this study, four systems (with different water contents) with an initially homogeneous distribution of the components were simulated at room temperature.…”
Section: Introduction and Reviewmentioning
confidence: 99%